2006
DOI: 10.1111/j.1471-4159.2006.04094.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of the rat carotid body chemoreceptors in ageing

Abstract: Some age-related deficits in the ventilatory responses have been attributed to a decline in the functionality of the carotid body (CB) arterial chemoreceptors, but a systematic study of the CB function in ageing is lacking. In rats aged 3-24 months, we have performed quantitative morphometry on specific chemoreceptor tissue, assessed the function of chemoreceptor cells by measuring the content, synthesis and release of catecholamines (a chemoreceptor cell neurotransmitter) in normoxia and hypoxia, and determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 47 publications
4
38
1
5
Order By: Relevance
“…The finding that changes in cAMP content at the CB in response to O 2 concentrations did not change with aging, suggests that the compensatory mechanism could occur within the CB as a whole. These results contrast with the reduction in carotid sinus nerve discharges in response to hypoxia observed in old rats (Conde et al 2006). It is known that the glossopharyngeal nerve has, in addition to carotid sinus nerve afferent fibers, a parallel autonomic parasympathetic efferent pathway sensitive to hypoxia that is the source of CB inhibition (Campanucci et al 2006).…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…The finding that changes in cAMP content at the CB in response to O 2 concentrations did not change with aging, suggests that the compensatory mechanism could occur within the CB as a whole. These results contrast with the reduction in carotid sinus nerve discharges in response to hypoxia observed in old rats (Conde et al 2006). It is known that the glossopharyngeal nerve has, in addition to carotid sinus nerve afferent fibers, a parallel autonomic parasympathetic efferent pathway sensitive to hypoxia that is the source of CB inhibition (Campanucci et al 2006).…”
Section: Discussioncontrasting
confidence: 54%
“…There is a consensual body of evidence about the changes in the morphology of the CB throughout aging: increase in extracellular matrix, reduction in number and volume of type I cells, and in the volume and density of mitochondria compared with young CB (Hurst et al 1985;Pokorski et al 2004;Conde et al 2006). These morphological findings do not apparently concur with the absence of functional impairment.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Therefore, it is suggested that the expression of TH mRNA returns to the control level after a sufficient amount of TH protein is secured. Conde et al (2006) reported that 280 dopamine content was increased by exposure to hypoxia in rat CB. Welsh et al (1978) suggested that dopamine suppressed ventilation through action of the CB.…”
mentioning
confidence: 99%